Fibroepithelial polyp/skin tag unusual presentation - A Case Report - Quamruzzaman, M; Das, KK; Khondoker, MS (Bangladesh Journal of Plastic Surgery, 2010)
An 18 year old female had presented with multiple skin tags all over her body. She is bearing these extensive skin tags since her very childhood. Her mother and younger sisters also have similar skin tags but not so extensive. So far the polyps were symptomless until she reached seventeen. At this time these grew excessively both in numbers and size, particularly at the cheek, nasolabial folds and lateral nasal wall of both sides. These also became infected and were very uncomfortable and unsightly. The lesion was biopsied and said Fibroepithelial polyp and there were no malignant changes. She was admitted in the ENT department of DMCH on 27-6-08 and was operated upon by joint team of Plastic and ENT Surgeons on 21-7-08. The polyps along with underlying skin was excised, full thickness graft was given to cover the defect. Donor site was medial aspect of right forearm. She was followed up for three months with no recurrence of the polyps in the grafted areas and graft color was satisfactory. Apart from mental retardation and frequent violent irrational behavior no other systemic illnesses was found in this patient. DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6491 Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.33-35